Men's Economic Dependency, Gender Ideology, and Stress at Midlife. Issue 3 (25th October 2019) - Kim, Joeun; Luke, Nancy
Abstract: Objective: This study investigates the association between men's economic dependency during midlife and allostatic load, an indicator of chronic stress, and how this relationship varies with men's gender ideology. Background: Women are primary breadwinners in almost a third of heterosexual couples in the United States. Emerging research finds that female primary breadwinning (or men's economic dependency) is a threat to masculinity that has negative implications for men's midlife health. However, there is no quantitative evidence of the mechanisms linking men's economic dependency and health, particularly the role of stress, and whether men's gender ideology moderates this relationship. Method: Using two waves of Midlife in the United States data for men who remained with the same marital or cohabiting female partner between waves ( N = 332), the authors estimate the relationship between men's economic dependency in Wave 1 and allostatic load in Wave 2. Results: There was no evidence of an association between men's economic dependency and higher allostatic load on average. However, gender ideology had a moderating influence; men's economic dependency was associated with higher allostatic load for those who espoused more traditional gender attitudes and lower allostatic load for those with the most egalitarian attitudes. Conclusion: The findings underscore the existence of multiple masculinities and suggest that economic dependence has a negative or positive influence on men's health depending on the meanings men attach to female primary breadwinning.